Integrated Management of Asian Soybean Rust - Zambolim, Laércio; Reis, Erlei Melo; Guerra, Wanderlei Dias; Juliatti, Fernando Cezar; Menten, José Otávio Machado (European Journal of Applied Sciences, 2022)
Asian soybean rust is caused by the biotrophic basidiomycete fungus Phakopsora pachyrhizi. The disease is considered as highly aggressive The disease is present in all countries that cultivate this legume. The disease is considered the one with the greatest destructive potential, causing damage ranging from 10 to 90%. In Brazil, the average damage attributed to asian soybean rust was 70% reported in the 2001/2002. P. pachyrhizi infect 41 species in 17 genera of the Fabaceae family. Experimentally it can infects 60 plant species belonging to 26 genera. Symptoms(lesions) in general are found on lower leaves, when the plants are in the phenological stage close to or after flowering. The uredia formed on the lesions progressively acquire a light brown to dark brown color which open into a tiny pore, expelling the hyaline colored urediniospores, which turn beige and accumulate around the pores or are removed by the wind. The final stage of the soybean rust epidemic is general yellowing of the foliage, with intense defoliation, reaching the complete fall of the leaves. The fungus causes TAN-type lesion, characterizing resistance and an RB-type lesion, highly susceptible to asian soybean rust. The stages of rust that occur in the field are uredia and telia. The pycnia, aecia and basidium stages have not yet been identified. The disease is favored by light and frequent rains, long dew periods and temperatures between 15 and 28 °C. Temperature higher than 30 °C limits P. pachyrhizi infection in soybean. Wind is the mais source of dissemination of the uredioniospores from the uredia. The greater of the frequency of hours in which the leaves remain wet, the greater the severity of the disease in the field. The latent period of the fungus varies from 7 to 14 days. Integrated control measures must be applied to control the disease. The following management strategies recommended are: use cultivars with horizontal resistance is the most important measure; use of early cycle cultivars; sowing at the beginning of the recommended season; elimination of voluntary soy plants in cotton, beans and corn plantations; absence of soybean cultivation in the off-season, through the sanitary vacuum (60 to 90 days); monitore of the crop from the end of vegetative stage (V9); monitore the temperature and rainfall to initiate the application; use of fungicides in compliance with anti-resistance strategies when symptoms appear according to the economic damage threshold. Multisite fungicides must be used in mixture with mobile penetrating fungicides with efficiency greater than 70%, to avoid selection of mutants in the population of the fungus in the field.